2020
DOI: 10.1108/ijchm-02-2020-0159
|View full text |Cite
|
Sign up to set email alerts
|

Successful restaurant crowdfunding: the role of linguistic style

Abstract: Purpose Crowdfunding can be an effective fundraising vehicle to independent restaurants to overcome fundraising limitations due to its small-size and high risk. A few studies have identified contents of communication for successful crowdfunding, yet missing is on how to say. The purpose of this paper is to investigate linguistics styles that are effective in pitches in restaurant crowdfunding. Design/methodology/approach The study analyzed 500 restaurant crowdfunding projects listed on Kickstarter.com that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 51 publications
1
39
2
Order By: Relevance
“…Positive framing increases agri-food campaign success, while negative framing is more effective for clean energy and climate preservation projects. These findings consolidate the stream of studies about the role of message framing in supporting the communication of green products (Amatulli et al , 2019; Borin et al , 2011; Grankvist et al , 2004; Karpinska-Krakowiak et al , 2020) and, specifically, the literature about the role of language in promoting new entrepreneurial projects (Kaminski and Hopp, 2020; Koh et al , 2020; Parhankangas and Renko, 2017; Zhou et al , 2015). Second, our study identifies other communication strategies, including the presence of quantitative results and a marked green emphasis in the project description, that affect the probability of success and thereby function as valuable tools for green companies seeking to attract supporters who are potentially predisposed to green marketing.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Positive framing increases agri-food campaign success, while negative framing is more effective for clean energy and climate preservation projects. These findings consolidate the stream of studies about the role of message framing in supporting the communication of green products (Amatulli et al , 2019; Borin et al , 2011; Grankvist et al , 2004; Karpinska-Krakowiak et al , 2020) and, specifically, the literature about the role of language in promoting new entrepreneurial projects (Kaminski and Hopp, 2020; Koh et al , 2020; Parhankangas and Renko, 2017; Zhou et al , 2015). Second, our study identifies other communication strategies, including the presence of quantitative results and a marked green emphasis in the project description, that affect the probability of success and thereby function as valuable tools for green companies seeking to attract supporters who are potentially predisposed to green marketing.…”
Section: Introductionsupporting
confidence: 76%
“…Despite the wide use of digital financial instruments by multiple organisations in this field, research that combines framing and the environmental literature is lacking (Jacobson et al, 2019), as is an application of framing theory to the entrepreneurial setting (Pan et al, 2020). Thus, our work expands upon both the crowdfunding literature about green campaign success determinants (Buttic e et al, 2019;Cumming et al, 2017;Kim and Hall, 2021;H€ orisch, 2018) and the literature about the importance of language in promoting new entrepreneurial projects and their funding activities (Kaminski and Hopp, 2020;Koh et al, 2020;Parhankangas and Renko, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the CF project pitches on Kickstarter are usually composed of textual description, visual images and/or videos prepared by the entrepreneurs. In the context of restaurant CF, Koh et al (2020) found that the linguistic styles of textual description have significant effects on CF success. They also found that follow-up communications (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Operationalization of linguistic style usually relies on LIWC, a coding dictionary that categorizes nearly 6,400 words into 89 themes ( Pennebaker et al, 2015 ; Kovacs and Kleinbaum, 2020 ). Eighteen out of these 89 themes directly capture linguistic style, and can be used to predict intentions or personality traits (e.g., Lee et al, 2019 ; Koh et al, 2020 ).…”
Section: Conceptualizing Internet Slang Stylementioning
confidence: 99%